A Crohn's Disease-associated IL2RA Enhancer Variant Determines the Balance of T Cell Immunity by Regulating Responsiveness to IL-2 Signalling. (12th June 2021) - Goldberg, Rimma; Clough, Jennie N; Roberts, Luke B; Sanchez, Jenifer; Kordasti, Shahram; Petrov, Nedyalko; Hertweck, Arnulf; Lorenc, Anna; Jackson, Ian; Tasker, Scott; Appios, Anna; Omer, Omer; et al.
Abstract: Background and Aims: Differential responsiveness to interleukin [IL]-2 between effector CD4 + T cells [Teff ] and regulatory T cells [Treg ] is a fundamental mechanism of immunoregulation. The single nucleotide polymorphism [SNP] rs61839660, located within IL2RA [CD25], has been associated with the development of Crohn's disease [CD]. We sought to identify the T cell immune phenotype of IBD patients who carry this SNP. Methods: Teff and Treg were isolated from individuals homozygous [TT], heterozygous [CT], or wild-type [CC] for the minor allele at rs61839660, and used for phenotyping [flow cytometry, Cytometry Time Of Flight] functional assays or T cell receptor [TCR] sequencing. Phosphorylation of signal transducer and activator of transcription 5 [STAT5] was assessed in response to IL-2, IL-7, and in the presence of basiliximab, a monoclonal antibody directed against CD25. Teff pro-inflammatory cytokine expression levels were assessed by reverse transcription quantitative polymerase chain reaction after IL-2 and/or TCR stimulation. Results: Presence of the minor T allele enhances CD25 expression, leading to increased STAT5 phosphorylation and pro-inflammatory cytokine transcript expression by Teff in response to IL-2 stimulation in vitro . Teff from TT individuals demonstrate a more activated gut homing phenotype. TCR sequencing analysis suggests that TT patients may have a reduced clonal capacity to mount an optimal regulatory T cell response. Conclusions: rs61839660 regulates the responsiveness of T cells to IL-2 signalling by modulating CD25 expression. As low-dose IL-2 is being trialled as a selective Treg modulator in CD, these findings highlight the potential for adverse effects in patients with this genotype. Graphical Abstract: